2021
DOI: 10.1038/s41467-021-26602-3
|View full text |Cite
|
Sign up to set email alerts
|

Within-host evolution of SARS-CoV-2 in an immunosuppressed COVID-19 patient as a source of immune escape variants

Abstract: The origin of SARS-CoV-2 variants of concern remains unclear. Here, we test whether intra-host virus evolution during persistent infections could be a contributing factor by characterizing the long-term SARS-CoV-2 infection dynamics in an immunosuppressed kidney transplant recipient. Applying RT-qPCR and next-generation sequencing (NGS) of sequential respiratory specimens, we identify several mutations in the viral genome late in infection. We demonstrate that a late viral isolate exhibiting genome mutations s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 35 publications
6
118
0
Order By: Relevance
“…However, lack of adherence to ART and development of drug resistance mutations leads to ongoing HIV replication, which, if left to persist for years, results in advanced HIV disease mediated immune suppression ( 28 ). We and others have recently shown that advanced HIV disease may lead to delayed clearance of SARS-CoV-2 and evolution of the SARS-CoV-2 virus ( 29 , 30 ), similar to what is observed in immune suppression caused by other factors ( 31 35 ).…”
supporting
confidence: 69%
“…However, lack of adherence to ART and development of drug resistance mutations leads to ongoing HIV replication, which, if left to persist for years, results in advanced HIV disease mediated immune suppression ( 28 ). We and others have recently shown that advanced HIV disease may lead to delayed clearance of SARS-CoV-2 and evolution of the SARS-CoV-2 virus ( 29 , 30 ), similar to what is observed in immune suppression caused by other factors ( 31 35 ).…”
supporting
confidence: 69%
“…Start of infection was taken to be the start of symptoms or the date of the first positive PCR test depending on what was available for each study. End of infection was the date of the final negative PCR test in the study (Avanzato et al 2020; Karim et al 2021; Stanevich et al 2021; Voloch et al 2020; Weigang et al 2021; Williamson et al 2021), death (Choi et al 2020) or when the individual was lost to follow up (Ramírez et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Because the Omicron variants are believed to have emerged in South Africa 1 , we speculate that some of these spike mutations may have been produced by long-term virus infections in immunocompromised patients. It was previously reported that evolution of SARS-CoV-2 in an immunosuppressed COVID-19 patient led to immune escape variants 45,46 . Deletions in NTD, for example, delY144, were detected in multiple immunosuppressed COVID-19 patients, which resulted in immune escape [45][46][47] .…”
Section: Co-infections Of Different Sars-cov-2 Variants In the Popula...mentioning
confidence: 96%
“…It was previously reported that evolution of SARS-CoV-2 in an immunosuppressed COVID-19 patient led to immune escape variants 45,46 . Deletions in NTD, for example, delY144, were detected in multiple immunosuppressed COVID-19 patients, which resulted in immune escape [45][46][47] .…”
Section: Co-infections Of Different Sars-cov-2 Variants In the Popula...mentioning
confidence: 96%